(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1998)
Conodonts from the lowermost Triassic Otoceras woodwardi beds and adjacent strata of Spiti are described and compared with Permian-Triassic (P-T) boundary bed faunas from elsewhere. A new pelagic zonation based on Neogondolella is introduced: the interval characterized by N. carinata-N. taylorae is subdivided into three parts based on successive first appearances of N. meishanensis, N. krystyni Orchard n. sp. and N. discreta Orchard and Krystyn n. sp., the nominal species of three successive zones. The development of these Griesbachian species involves a progressive morphological change in the configuration of the axial part (blade-carina-cusp) of the pectiniform elements. The pelagic conodont zonation is intercalibrated with the parallel zonation based on species of Hindeodus and Isarcicella, and with ammonoid faunas from Spiti, other Himalayan localities, and the Arctic. The meishanensis Zone embraces the parvus Zone and part of the overlying staeschei Zone. Strata containing O. woodwardi in Spiti carry the indices to the staeschei and krystyni zones. The Neogondolella conodont fauna associated with Otoceras differs from that of the latest Permian Changshing Limestone of China, but resembles that from the P-T boundary transition beds at Meishan, where a meishanensis Zone of restricted scope occurs beneath the parvus datum. The faunal change which introduces the characteristic Neogondolella species of the N. carinata-N. taylorae fauna occurs at the base of the P-T boundary transition beds at Meishan, the proposed boundary stratotype. Slightly above this level, the disappearance of most Neogondolella species and the introduction of new Hindeodus species coincides with a change in conodont biofacies rather than an extinction event. In the Spiti sections, the N. carinata-N. taylorae fauna, associated at first with H. parvus (as in Selong, Tibet), persists through the entire Griesbachian. Indices of the three Neogondolella zones are also recognized in the Salt Range and the Canadian Arctic. Four new conodont species are described: Neogondolella discreta, N. kazi, N. krystyni, and N. nassichuki.